The RNA-binding Protein RNPC1 Stabilizes the mRNA Encoding the RNA-binding Protein HuR and Cooperates with HuR to Suppress Cell Proliferation - Cho, Seong-Jun (American Society for Biochemistry and Molecular Biology, 2012)
The RNA-binding protein HuR, a member of the embryonic lethal abnormal vision/Hu protein family, plays a critical role in many cellular processes, including cell proliferation, angiogenesis, and inflammatory response. Despite significant progresses in understanding how HuR functions, the mechanism by which HuR expression is controlled is still poorly understood. Here, we showed that RNA-binding protein RNPC1 post-transcriptionally regulates HuR expression via mRNA stability. Specifically, we showed that overexpression of RNPC1 increases, whereas knockdown or knock-out of RNPC1 decreases, the level of HuR transcript and protein. Moreover, we showed that RNPC1, but not mutant RNPC1 deficient in RNA binding, stabilizes HuR transcript via binding to its 3′-untranslated region. Furthermore, to determine the biological significance of RNPC1-enhanced HuR expression, we showed that HuR, by repressing c-Myc expression, facilitates RNPC1-mediated growth suppression. Together, we have uncovered a novel mechanism by which HuR is regulated by RNPC1 via mRNA stability and HuR is a mediator of RNPC1-induced growth suppression.